Peningkatan Kemampuan Membaca Pemahaman Siswa Kelas III Melalui Metode Pembelajaran SQ3R di SDN 1 Jatimulya Kab. Lebak - Purwatiningsih, Sri; Arini, Ira; Mualimah, Eka Nurul; Aryadi, DC; Salim, Agus (LP. Ma'arif Janggan Magetan, 2024)
Reading comprehension is a fundamental skill that must be mastered by elementary school students. However, many students still have difficulty in understanding the contents of the reading as a whole. This study aims to analyze the application of the Survey, Question, Read, Recite, Review (SQ3R) learning model in improving the reading comprehension of grade III students at SDN 1 Jatimulya. The research method used is descriptive qualitative, with grade III teachers and grade III students as research subjects. Data collection techniques include observation, interviews, tests, and documentation. The data obtained were analyzed using data reduction techniques, data presentation, and drawing conclusions/verification developed by Miles and Hubberman. The results of the study showed that the application of the SQ3R learning method can improve students' reading comprehension. A total of 8 students obtained an average score of 75, which is classified as good. Meanwhile, 6 students still had difficulty in understanding the reading, with a percentage of 42.8%. This difficulty is caused by minimal motivation and interest in reading, difficulty concentrating, limited reading materials owned by students, and inadequate school facilities and infrastructure.